Towards good e-flows practices in the small-scale hydropower sector in Uganda - O'Brien, G.C.; Dickens, Chris W. S.; Mor, C.; England, M. I. (Frontiers Media, 2021)
Stakeholders of the small-scale (<50 MW generation capacity) hydropower sector in Uganda recognise the importance of sustainable development of the resources that have social and ecological importance. Uganda is experiencing a boom in hydropower projects resulting in over generation of electricity and its exportation to neighbouring nations. Limited policies are currently available in Uganda to direct the sustainable development of this sector. Environmental flows (e-flows) practices established for the Nile Basin region and international good e-flows practices can contribute to sustainable management of hydropower developments in Uganda. The paper defines and explains e-flows, identifies water resource attributes of importance for e-flows determination associated with hydropower and threat associated with this activity in Uganda, and provides good e-flows determination and management practices based on regional and international information. The determination and management of e-flows in the hydropower sector in Uganda is largely dependent on the availability of and quality of hydrology, hydraulic and flow-ecosystem and flow-ecosystem service relationship information. This review of good-practice e-flows practice for the small hydropower sector in Uganda provides guidance to support multiple stakeholders of water resources in Uganda for a better future for all of its vulnerable communities and the environments they depend on.